2014
DOI: 10.1039/c4cc00928b
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism control of an active pharmaceutical ingredient beneath calixarene-based Langmuir monolayers

Abstract: This communication demonstrates the possibility to nucleate and grow different crystalline polymorphic forms of gabapentin (GBP) using, as nucleation templates, Langmuir monolayers of an amphiphilic calixarene at different packing densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
4
15
0
Order By: Relevance
“…In addition, the isotherm reveals the presence of a phase transition at 39 mN m −1 , suggesting that a molecular rearrangement of the film occurs, consistent with previously reported results. 27 In the presence of 10 −5 M aqueous CoCl 2 , NiCl 2 , and MnCl 2 subphases, the collapse pressure (55, 51, and 51 mN m −1 , respectively) and A 0 (113, 126, and 125 Å 2 molecule −1 , respectively) values are fairly close to that measured on pure water (π c = 51 mN m −1 , A 0 = 122 Å 2 molecule −1 ). The rigidity of Langmuir monolayers is typically defined by its compressibility modulus:…”
Section: ■ Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, the isotherm reveals the presence of a phase transition at 39 mN m −1 , suggesting that a molecular rearrangement of the film occurs, consistent with previously reported results. 27 In the presence of 10 −5 M aqueous CoCl 2 , NiCl 2 , and MnCl 2 subphases, the collapse pressure (55, 51, and 51 mN m −1 , respectively) and A 0 (113, 126, and 125 Å 2 molecule −1 , respectively) values are fairly close to that measured on pure water (π c = 51 mN m −1 , A 0 = 122 Å 2 molecule −1 ). The rigidity of Langmuir monolayers is typically defined by its compressibility modulus:…”
Section: ■ Results and Discussionsupporting
confidence: 59%
“…In addition, the π c increases from 51 up to 62 mN m −1 , a considerably high value for a monomolecular film formed by a calixarene-based amphiphile. Furthermore, the characteristic phase transition observed on water is absent for Cu 2+ solution at 10 −5 M. These observations indicate that Cu 2+ , Co 2+ , Ni 2+ , and Mn 2+ ions interact with the monolayer even at a relatively low concentration of 10 −5 M. In a previous work, 27 we showed that, in the solid state, 1 adopts a pinched cone conformation whereby two distal phenyl rings are splayed apart and the other two are closer to each other. The amphiphiles are self-assembled in a bilayered fashion where the carboxylic groups of adjacent macrocycles are arranged side-by-side.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…Cyclodextrins have been used to form inclusion complexes with a group of polymers, given that, by being appropriately removed, the host is forced to coalesce into a pure polymeric solid, favoring the polymorph whose structure is the most extended [65]. In the same way, using monolayers of amphiphilic calixarenes favors the formation of specific polymorphs of gabapentin [66]. An interesting application is the design of an organic semiconductor, consisting of a polymorph and a nanoprinted polyimide layer [67].…”
Section: Nucleation and Polymorphismmentioning
confidence: 99%
“…2 One should point out the use of calixarenes in the biological field 3,4 and in design of pharmaceutic agents. [5][6][7] Calixarenes form metal nanoparticles, [8][9][10] e.g. AuNPs 8,9 and AgNPs, 10 as well as organic NPs, 11 and serve for construction of sensors; [12][13][14] they also may be used as extractants of f-elements.…”
Section: Introductionmentioning
confidence: 99%